Taran wanderer - Alexander, Lloyd (Alexander, Lloyd. Chronicles of Prydian, 2017)
Taran is an Assistant Pig-Keeper no longer he has become a hero. Now he dreams of winning the hand of Princess Eilonwy, but how can someone who has spent his whole life caring for a pig hope to marry royalty? Eager to learn his origins and hoping to discover noble roots, Taran sets off with the faithful Gurgi. The journey takes the companions to the three witches in the Marshes of Morva and through the many realms of Prydain. At last they reach the mystical Mirror of Llunet, which reveals a person's true identity. Yet Taran may not be ready to face the truth.